Collecting, Collage, and Alchemy: The Harry Smith Anthology of American Folk Music as Art and Cultural Intervention - Moist, Kevin M. (American Studies, 2010)
In 1952 Folkways Records released a series of compilations of early 20th century music titled The Anthology of American Folk Music, assembled by artist and record collector Harry Smith. A major influence on the folk revival of the 1950s, the Anthology was also an artwork in itself, one that challenged a range of conventional assumptions about not only music but also broader social and cultural processes. Smith’s strategy in constructing the Anthology combined the practice of collecting, collage aesthetics, and the philosophy of alchemy, transmuting seemingly simple materials (recordings of folk music of the 1920s and 1930s) into new and different forms that suggested fresh cultural possibilities grounded in these seemingly “lost” traditions. This article discusses the Anthology in terms of its cultural and aesthetic approaches, with a particular focus on their relevance for and continuing influence on contemporary postmodern culture.